Organizational Mindfulness and its Interactive Effect on the Relationship between Strategic Capital and Proactive Career Behavior: An Analytical Study of the Prespectives of a Sample of Lecturers at Knowledge University - Erbil - Ava Omer Fatah; Lask Arsalan Bayiz; Zana Majed Sadq; Media Aras Mohammed Saeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The current study aims to determine and analyze the interactive effect of Organizational Mindfulness on the relationship between Strategic capital and proactive career behavior at Knowledge University in Erbil city. The analytical descriptive method was adopted to describe the theoretical framework for the concepts and variables of the study, and then analyze the correlation relationship and effect between the dependent and independent variable on the one hand, and the interactive variable and its effect on the assumed relationship between the other two variables on the other hand. The researchers used the questionnaire survey as a tool to collect primary data from the study sample taken from the study population represented 53 of teaching staff in the field of study, which is Knowledge University in Erbil. The SPSS program Version 22 was adopted to analyze the required statistical analyzes such as the frequencies in addition to find the values of mean and standard deviations for the dimensions of the study variables along with testing the study hypotheses using the Pearson correlation coefficient and the Simple Regression analysis. This study found that there is a statistically significant correlation and regression relationship between the study variables and their dimensions in the researched from the perspective of their teaching staff on the one hand, and this relationship is affected by the action of the interactive variable influenced by statistical significance on the other side according to the results of statistical analyzes which is useful to prove study hypotheses. The study presented a set of recommendations, including the need for the university to rely more on organizational mental alertness because of its interactive effect in strengthening the existing relationship between strategic capital and proactive career behavior.